Ichthyofauna diet changes in response to urbanization: the case of upper Paranapanema River basin (Brazil) - Peressin, Alexandre; da Silva Gonçalves, Cristina [UNESP]; Cetra, Mauricio (Springer Nature, 2018)
Alterations in stream environments can alter fish food availability, but there is little research data related to the impacts of urbanization on fish diets in tropical streams. Thus, we sought to compare the diet of ten fish species in urbanized and non-urbanized streams reaches. Fish stomach contents were obtained for four urban and five non-urban stream reaches from two medium-sized cities. We verified the similarity of diet composition from urbanized/non-urbanized streams. In-stream features mainly related to the substrate highlighted a perturbation gradient: gravel, pebbles and cobbles were associated to the wider urban reaches while silt were representative in the narrow pools from non-urban streams. Fishes changed their diet in response to urban and non-urban treatments. Omnivorous fishes consumed more detritus and Chironomidae and less terrestrial adult insects in urban reaches, while invertivorous fish consumed more terrestrial adult insects and Trichoptera larvae in the non-urbanized stream reaches. Although the management of the physical structure of streams in Brazil has been basically focused on riparian reforestation, our results suggest that a restoration plan for urban streams cannot be limited to reforestation of its surroundings, but also need to consider the physical structure of the channel, especially the substrate, which contributes to promote in-stream variability.
Keywords: Chironomidae; Detritus; Invertivorous; Omnivorous